2019
DOI: 10.1016/j.jval.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of a Mobile Mammography Unit for Breast Cancer Screening to Reduce Geographic and Social Health Inequalities

Abstract: Background: Breast cancer is the leading cancer in terms of incidence and mortality among women in France. Effective organized screening does exist, however, the participation rate is low, and negatively associated with a low socioeconomic status and remoteness.Objectives: To determine the cost-effectiveness of a mobile mammography (MM) program to increase participation in breast cancer screening and reduce geographic and social inequalities.Methods: A cost-effectiveness analysis from retrospective data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…21 In addition, mobile screening units demonstrated cost-effectiveness in increasing cancer screening rates, especially among underserved populations. [22][23][24][25] Collaboration with mobile screening units can expand access to cancer screening in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, mobile screening units demonstrated cost-effectiveness in increasing cancer screening rates, especially among underserved populations. [22][23][24][25] Collaboration with mobile screening units can expand access to cancer screening in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common cancer among women, with psychological, occupational and social consequences. [ 12 ] This prospective, cross-sectional study was to evaluate the preoperative stress levels in patients undergoing breast cancer surgery. Diagnosis and treatment, as well as the consequences on women's everyday life, are often severe.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Therefore, organized screening programs may have the potential to eliminate at least some barriers encountered by disadvantaged women and reduce inequities. 31 , 32 Assuming that mobile mammography units help to increase participation, 33 36 we showed that this strategy would be cost-effective in regions with low screening adherence. Moreover, earlier studies 33 showed that decreasing geographical barriers is also an effective measure for decreasing social inequalities in participation in breast cancer screening for the total population.…”
Section: Discussionmentioning
confidence: 86%